2021
DOI: 10.3389/fendo.2021.626390
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Enhanced Diabetic Renal Tubular Injury via HIF-1α/HO-1 Pathway in db/db Mice

Abstract: BackgroundFerroptosis is a recently identified iron-dependent form of cell death as a result of increased reactive oxygen species (ROS) and lipid peroxidation. In this study, we investigated whether ferroptosis aggravated diabetic nephropathy (DN) and damaged renal tubules through hypoxia-inducible factor (HIF)-1α/heme oxygenase (HO)-1 pathway in db/db mice.MethodsDb/db mice were administered with or without ferroptosis inhibitor Ferrostatin-1 treatment, and were compared with db/m mice.ResultsDb/db mice showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(125 citation statements)
references
References 50 publications
5
118
2
Order By: Relevance
“…Notably, we found that ferroptosis was increased in HFD-challenged mice subjected to LPS stimulation. To date, studies have reported that ferroptosis can be activated in diabetes [28] and LPS stimulation [29]. However, in the present study, we found that renal ferroptosis elicited no significant effect in HFD-challenged mice without LPS stimulation.…”
Section: Discussioncontrasting
confidence: 87%
“…Notably, we found that ferroptosis was increased in HFD-challenged mice subjected to LPS stimulation. To date, studies have reported that ferroptosis can be activated in diabetes [28] and LPS stimulation [29]. However, in the present study, we found that renal ferroptosis elicited no significant effect in HFD-challenged mice without LPS stimulation.…”
Section: Discussioncontrasting
confidence: 87%
“…The role of ferroptosis in the development of DN is also supported by the finding that treatment with high glucose led to ferroptosis-specific mitochondrial changes in the HK-2 cells, whereas treatment with Fer-1 significantly rescued these changes and alleviated the renal pathological injuries in diabetic DN mice through Nrf2 pathway [74]. Treatment with Fer-1 also significantly ameliorated kidney hypertrophy and albuminuria to reduce the intracranial accumulation of lipid peroxidation in the diabetic mice by the HIF-1α/HO-1 pathway [75]. In addition, it has also been reported that HO-1 is expressed specifically in glomeruli in DN, and the induction of HO-1 prevents podocyte apoptosis [76,77].…”
Section: The Roles Of Ferroptosis In Ckdmentioning
confidence: 80%
“…In addition, induction of HIF-1 by EGFR can make A549 lung cancer cells resistant to another type of PCD called anoikis under the lipid raft-disrupting stress (45). Emerging evidence also supports the role of HIFs in the induction of ferroptosis (46,47). Jiang et al…”
Section: Hif-1amentioning
confidence: 97%